Expertise Redundancy, Transactive Memory, and Team Performance in Interdisciplinary Care Teams - Zhu, Xi (Health Serv Res, 2018)
OBJECTIVE: To examine how expertise redundancy and transactive memory (TM) in interdisciplinary care teams (ICTs) are related to team performance. DATA SOURCES/STUDY SETTING: Survey and administrative data were collected from 26 interdisciplinary mental health teams. STUDY DESIGN: The study used a longitudinal, observational design. Independent variables were measured at baseline, 6, and 12 months: expertise redundancy (the extent to which team members possess highly overlapping knowledge), TM accuracy (the extent to which team members accurately recognize experts in relevant knowledge domains), and TM consensus (the extent to which team members agree on who is expert in which knowledge domain). Team performance was measured as risk‐adjusted average number of client hospitalization for the 6 months following each survey. DATA COLLECTION METHODS: Survey data were collected by the authors. Administrative data were collected by the state's administrative agency. PRINCIPAL FINDINGS: Expertise redundancy had a negative effect on performance. TM accuracy had a positive effect on performance, and such effect was stronger when expertise redundancy was higher. No significant effect was found on TM consensus. CONCLUSIONS: Transactive memory could serve as a cognitive coordination mechanism for mitigating the negative effect of complex knowledge structure in ICTs.